Qur'anic Narratives of Women's Competencies and The Consequences of Islamic Law on Their Involvement in Society - Miswar, Andi; R, Abd Rahman; HM, M. Amir; Fakhrurrazi, Fakhrurrazi; Mukhtar, Makmunzir (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Many people continue to believe that the Islamic Law perspective of women differs from men, which tends to be based on subordinate doctrines. However, in the al-Qur'an, divine revelation proclaims that women also have Competencies which is demonstrated by various forms of narration in the language style of the Qur'an along with their prowess in the public sector based on social reality. This paper discusses the main problem, namely the competence of women in the Qur'an from the perspective of Islamic law and their work in society. This research uses a qualitative research type with the method of text analysis of the verses of the Qur'an with an interpretive science approach, as well as analysis of field data regarding the role of women in various sectors of life from the perspective of Islamic law. Data was collected through a literature study and in-depth interviews with several informants in various regions of Indonesia. The research concluded that women's competence is mentioned in the narration of the Qur’an with uslub and various language styles, showing that women have superiority and toughness according to their nature and identity. They act with the capital of intellectual, emotional, and spiritual intelligence as well as physical and psychological strength. Furthermore, women's involvement in the public sector provides clear evidence of women's abilities relevant to the verses of the Qur’an and refutes subordinate perspectives of them. Islamic law perspective recommends building a perfect mutualism symbiotic, respectful, civilized, and progressive.